RELATIONSHIPS OF FERNS IN THE POLYPODIACEAE FAMILY IN THE BUKIT KUJAU AREA, TEMPUNAK DISTRICT, SINTANG REGENCY, BASED ON MORPHOLOGICAL CHARACTERISTICS - Juniarty, Syffa; Rafdinal, Rafdinal; Ifadatin, Siti (RUMPHIUS, 2024)
Ferns belonging to the Polypodiaceae family are widely distributed across various regions of the world, particularly in forested areas and regions characterized by high humidity levels. The analysis of relationships among ferns can be conducted based on their morphological characteristics. The aim of this study was to determine the relationships among ferns of the Polypodiaceae family in the Bukit Kujau area of Tempunak District, Sintang Regency, utilizing morphological traits. This research was conducted from October to December 2023, during which 35 samples were collected in the Bukit Kujau area through purposive sampling. The relationships were analyzed using the UPGMA method in the NTSys program. The study identified seven species of ferns from the Polypodiaceae family: Platycerium bifurcatum (Cav.), Dynaria querfolia (L.), Davallia denticulatum (Burm.f.), Phymatodes scolopendria (Burm.), Diplazium esculentum (Rezt.), Pyrrosia numularifolia (Sw.), and Drymoglossum piloselloides (Linn.). Based on the grouping analysis, the seven species of ferns exhibited a similarity coefficient ranging from 0.37 to 1.00. At a similarity coefficient of 0.47, the species were grouped into three clusters, each distinguished by morphological characteristics such as sorus shape, sorus type, and sorus color.